Gender equity in the boardroom : the case of India - Kumar, Payal; Singh, Ganesh (Emerald Publishing Limited, 2020)
Gender diversity in boardrooms across India remain below the global average. This book analyses gender representation across industries and focus on the issue of low female representation by interviewing board members, executives and managers.
Includes index.
Keywords: Women lawyers -- India.; Sex discrimination in employment -- India.; Law -- General.; Gender & the law.; elektronické knihy; electronic books